2019
DOI: 10.1093/nar/gkz976
|View full text |Cite
|
Sign up to set email alerts
|

Potent and sustained huntingtin lowering via AAV5 encoding miRNA preserves striatal volume and cognitive function in a humanized mouse model of Huntington disease

Abstract: Huntington disease (HD) is a fatal neurodegenerative disease caused by a pathogenic expansion of a CAG repeat in the huntingtin (HTT) gene. There are no disease-modifying therapies for HD. Artificial microRNAs targeting HTT transcripts for degradation have shown preclinical promise and will soon enter human clinical trials. Here, we examine the tolerability and efficacy of non-selective HTT lowering with an AAV5 encoded miRNA targeting human HTT (AAV5-miHTT) in the humanized Hu128/21 mouse model of HD. We show… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
57
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 45 publications
(58 citation statements)
references
References 77 publications
1
57
0
Order By: Relevance
“…Antisense oligonucleotides are being administered into the cerebrospinal fluid, 82 which will superfuse the cortex well, and need to diffuse to the striatum. By contrast, adeno-associated virus ribonucleic acid interference reagents shown to be effective in mice 83 will be injected into deep brain structures especially the striatum in human subjects and will need to be transported to the cortex. The fMRI method described here may provide a means to determine metabolic and microvascular abnormalities in the brain regions differentially targeted by these strategies.…”
Section: Discussionmentioning
confidence: 99%
“…Antisense oligonucleotides are being administered into the cerebrospinal fluid, 82 which will superfuse the cortex well, and need to diffuse to the striatum. By contrast, adeno-associated virus ribonucleic acid interference reagents shown to be effective in mice 83 will be injected into deep brain structures especially the striatum in human subjects and will need to be transported to the cortex. The fMRI method described here may provide a means to determine metabolic and microvascular abnormalities in the brain regions differentially targeted by these strategies.…”
Section: Discussionmentioning
confidence: 99%
“…The resulting mutant huntingtin (mHTT) protein disrupts many cellular processes, ultimately leading to neurodegeneration (reviewed in 2 ). Numerous preclinical studies have demonstrated that lowering HTT in the brain can prevent or even reverse HD-like behavioral and neuropathological phenotypes in rodent models of HD [3][4][5][6][7][8][9][10][11][12][13] , leading to advancement of HTT lowering agents into clinical trials for the treatment of HD (NCT03761849, NCT03225833, NCT03225846, NCT04120493). Clinical translation of HTT lowering therapies has necessitated the identification of biomarkers to assess HTT target engagement in the central nervous system (CNS).…”
Section: Introductionmentioning
confidence: 99%
“…We were curious to identify modifiers that concordantly affect mHTT-induced pathogenesis in both neurons and glia as these might be particularly attractive therapeutic targets for HD. We were particularly interested to discover whether any such shared modifiers exert their effect by reducing mHTT levels, which is considered a promising approach to therapy ( Al-Ramahi et al, 2018 ; Barker et al, 2020 ; Caron et al, 2020 ; Li et al, 2019 ; Tabrizi et al, 2019 ; Wang et al, 2014 ; Wood et al, 2018 ; Yamamoto et al, 2000 ; Yao et al, 2015 ). We therefore again integrated network analysis with high-throughput experimentation.…”
Section: Resultsmentioning
confidence: 99%